Norm inflation for the generalized Boussinesq and Kawahara equations. (July 2017) - Okamoto, Mamoru
Abstract: We consider ill-posedness of the Cauchy problem for the generalized Boussinesq and Kawahara equations. We prove norm inflation with general initial data, an improvement over the ill-posedness results by Geba et al. (2014) for the generalized Boussinesq equations and by Kato (2011) for the Kawahara equation.